2011
DOI: 10.1037/a0022425
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between adult attachment style and therapeutic alliance in individual psychotherapy: A meta-analytic review.

Abstract: The present study examined the relationship between adult attachment style and therapeutic alliance in individual psychotherapy. Search procedures yielded 17 independent samples (total N = 886, average n = 52, standard deviation = 24) for inclusion in the meta-analysis. Results indicated that greater attachment security was associated with stronger therapeutic alliances, whereas greater attachment insecurity was associated with weaker therapeutic alliances, with an overall weighted effect size of r = .17, p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
154
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(169 citation statements)
references
References 62 publications
7
154
1
7
Order By: Relevance
“…This way, OT could potentially enhance motivation for treatment, as well as the therapeutic alliance (Olff et al, 2010). Strength of therapeutic alliance, defined as the affective bond between the therapist and patient, is an important and consistent predictor of treatment success (Ormhaug et al, 2014) and depends on the patient's attachment security: more secure attachment is related to stronger therapeutic alliance and vice-versa (see Diener and Monroe, 2011 for a metaanalysis). Attachment style may be particularly relevant in PTSD: insecure attachment, has been associated with higher PTSD symptom severity in trauma-exposed individuals (see Woodhouse et al, 2015 a meta-analysis).…”
Section: Discussionmentioning
confidence: 99%
“…This way, OT could potentially enhance motivation for treatment, as well as the therapeutic alliance (Olff et al, 2010). Strength of therapeutic alliance, defined as the affective bond between the therapist and patient, is an important and consistent predictor of treatment success (Ormhaug et al, 2014) and depends on the patient's attachment security: more secure attachment is related to stronger therapeutic alliance and vice-versa (see Diener and Monroe, 2011 for a metaanalysis). Attachment style may be particularly relevant in PTSD: insecure attachment, has been associated with higher PTSD symptom severity in trauma-exposed individuals (see Woodhouse et al, 2015 a meta-analysis).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with research on the association between avoidant attachment and the therapeutic alliance in individual therapy, where many of the studies did not differentiate between anxious and avoidant attachment. For example, the meta-analysis that examined attachment and alliance in individual therapy (Deiner & Monroe, 2011) lumped these two types of attachment into the single category: insecure attachment. However, studies that have differentiated between the two types of insecure attachment, have generally found a lack of association between anxious attachment and the therapeutic alliance.…”
Section: Discussionmentioning
confidence: 99%
“…One consistent finding in the general psychotherapy literature is that the quality of clients' current or past attachment relationships predicts the quality of therapeutic relationships. A number of studies have found that clients who have secure attachment styles and are comfortable with close emotional relationships develop better alliances (Diener and Monroe, 2011;Smith et al, 2010). Attachment styles may be related to improved therapy outcomes as a result of their associations with therapeutic alliance; a recent study involving people with early psychosis found associations between insecure attachment and poorer recovery from symptoms 12 months later (Gumley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%